THE INFLUENCE OF STOCKING DENSITY AGAINST SURVIVAL RATE OF CATFISH (Clarias gariepinus) ON RECIRCULATION SYSTEM - santoso, anjas adi; muarif, muarif; rosmawati, rosmawati (Jurnal Mina Sains, 2018)
One of the technologies to keep the water quality remains optimal ias a recirculation system. This research is aimed to determine the influence of denisity of catfish (Clarias gariepinus) on the recirculation system. Fish test used is catfish fry the age of 2 weeks with average weight 0.58 g and an average length of 2.7 cm as much as 10,000 fish. The experimental research used completely randomized design with 4 treatments and 3 replications. The treatments were A (20 fish/liter of water), B (30 fish/liter of water), C (40 fish/liter of water) and D (50 fish/liter of water). The survival rate, the feed efficiency, and water quality has been observed. The results of research showed that the survival rate and the feed efficiency were significantly different (P<0.05). The highest survival rate in this research was in the treatment A (20 fish/liter of water) that was 70.5%. The stocking density of catfish fry of 20 fish/liter of water can be used as basis forÂ  the maintenance of catfish fry for reach the optimal survival rate.Â Key words: Catfish, survival rate, feed efficiency, recirculation